Widespread global enhancement of vegetation resistance to compound dry-hot events due to anthropogenic climate change - Tian Yao; Chuanhao Wu; Pat J.-F. Yeh; Bill X. Hu; Yufei Jiao; Qiongfang Li; Jie Niu (Ecological Indicators, 2025)
Compound Dry-Hot (CDH) events, the simultaneous occurrence of drought and high temperature events, have become more frequent under recent global warming, posing a serious threat to terrestrial vegetation. However, the role of anthropogenic climate change (ACC) signals in the characteristics of CDH events, and its consequence to vegetation vulnerability, are still poorly understood. Based on the meteorological data and simulated Leaf Area Index (LAI) data from four CMIP6 models under the “natural-only” (NAT) and “natural and anthropogenic” (ALL) experiments, this study investigates the ACC impacts on historical (1982–2014) occurrence of CDH (with different intensities and durations) and quantifies the anthropogenic signals in vegetation vulnerability by using the Fraction of Attributable Risk method. The results show that ACC not only increases the frequency and duration of CDH over most global regions, also simultaneously causes a globally widespread increase in vegetation resistance to CDH (particularly in the Southern Hemisphere), which reduces the probability of vegetation loss (defined as LAI ≤ 40th percentile) by 7.2∼19.6 % on global average. Moreover, vegetation resistance generally increases with CDH intensity globally, mainly due to the expanded vegetation coverage and the alleviation of high-temperature inhibitory effects on vegetation growth. We also find that ACC increases the vulnerability of Tundra and Taiga to CDH only in northern high-latitudes due to the decreased vegetation coverage, but enhances the grassland resistance to CDH to a lesser extent than forests due to the greater physiological burden brought by CDH to grasslands than to forests. These findings suggest that climate adaptation strategies should prioritize vegetation protection in high-latitudes and promote drought- and heat-resilient vegetation types in grassland and semi-arid regions in order to enhance ecosystem stability under future CDH extremes.